2015
DOI: 10.20897/lectito.201502
|View full text |Cite
|
Sign up to set email alerts
|

Fish in the Classroom: A Survey of the Use of Aquaponics in Education

Abstract: School gardens and demonstration farms are exciting avenues for experiential learning in education. Aquaponics, the combination of aquaculture and hydroponics, is an attractive educational tool because systems are self-contained ecosystems that allow teachers and students to explore a wide range of science, technology, engineering, and mathematics (STEM) topics. The aim of this study was to characterize the use of aquaponics in education in the United States (US) using an online survey. One hundred respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
1
16
0
5
Order By: Relevance
“…Aquaponics, the combined culture of fish and plants in recirculating water systems was pioneered in the 1970s ( Sneed et al, 1975 ; Naegel, 1977 ; Lewis et al, 1978 ) as an environmentally sustainable agricultural method based on the concepts of minimal water use and minimal impact on environmental water quality compared to traditional agricultural methods ( Blidariu and Grozea, 2011 ). In addition to producing salable crops, aquaponics is valued for its positive development of community and economic opportunity in urban areas ( Goodman, 2011 ), and its wide-ranging educational benefits for students through the post-secondary level ( Hart et al, 2014 ; Genello et al, 2015 ). Despite these benefits, microbial research supporting aquaponic crop production lags behind traditional agricultural systems.…”
Section: Aquaponics – Stripping Away the Soilmentioning
confidence: 99%
“…Aquaponics, the combined culture of fish and plants in recirculating water systems was pioneered in the 1970s ( Sneed et al, 1975 ; Naegel, 1977 ; Lewis et al, 1978 ) as an environmentally sustainable agricultural method based on the concepts of minimal water use and minimal impact on environmental water quality compared to traditional agricultural methods ( Blidariu and Grozea, 2011 ). In addition to producing salable crops, aquaponics is valued for its positive development of community and economic opportunity in urban areas ( Goodman, 2011 ), and its wide-ranging educational benefits for students through the post-secondary level ( Hart et al, 2014 ; Genello et al, 2015 ). Despite these benefits, microbial research supporting aquaponic crop production lags behind traditional agricultural systems.…”
Section: Aquaponics – Stripping Away the Soilmentioning
confidence: 99%
“…The main challenge in designing courses at higher education level is the interdisciplinary nature of aquaponics, as prior knowledge of both aquaculture and horticulture is essential. While some studies investigated the use of aquaponics in education (Hart et al 2013;Hart et al 2014;Junge et al 2014;Genello et al 2015) and a number of on-line courses are available, a course outline for aquaponics at the tertiary level at a main-stream does not yet exist, or at least hasn't been published. For tertiary level aquaponics courses to be implemented in the EU, the Bologna Process, which underlines the need for meaningful implementation of learning outcomes in order to consolidate the European Higher Education Area (EHEA), Fig.…”
Section: Aquaponics In Higher Educationmentioning
confidence: 99%
“…Hence, the information needed to evaluate the impact of aquaponics classes on meeting the objectives of the students' curricula is still missing. In a survey on the use of aquaponics in education in the USA (Genello et al 2015), respondents indicated that aquaponics were often used to teach subjects, which are more exclusively focused on STEM topics. Aquaponics education in primary and secondary schools is science-focused, project-oriented, and geared primarily toward older students, while college and university aquaponics were generally larger and less integrated into the curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethical benefits of aquaponics extend beyond sustainability. They can provide local healthy food and jobs in urban settings (Proksch et al 2019) and support teaching of common curricular topics such as plant growth and nutrient cycles whilst creating nature experiences for children (Genello et al 2015). They also can serve as social projects for disadvantaged groups or as communitybuilding projects (Hart et al 2013).…”
Section: Introductionmentioning
confidence: 99%